Designing an Integrated English Learning Mobile Application Using a User-Centered Approach - Nabiilah Lintang Dadari; Rizki Hikmawan (Jurnal Paedagogy, 2026)
This study aims to address the fragmentation of learner experiences by developing an integrated mobile application that consolidates core English language skills—such as grammar, speaking, and vocabulary—into a single, holistic learning ecosystem using a User-Centered Design (UCD) approach. Data were collected from ten participants across three rounds of testing, comprising interviews and two iterative usability evaluation cycles employing the Cognitive Walkthrough (CW) method, the System Usability Scale (SUS), and the User Experience Questionnaire (UEQ). Quantitative data from the SUS and UEQ were analyzed descriptively to examine usability improvements across iterations, while qualitative data from interviews and observational notes were thematically coded to identify usability issues and user preferences. The results indicate consistent improvements across the two evaluation rounds. Specifically, CW success rates increased from 89.23% to 96.92%, SUS scores improved from 71.8 to 78.6—placing the application within the “good” usability category—and all UEQ dimensions showed enhancement, with an average score of 1.92, classified as “high positive.” These findings demonstrate that the iterative application of the UCD approach effectively enhances usability and user satisfaction. Overall, the final integrated design successfully establishes a synergistic and holistic mobile learning ecosystem for English language learning.